The impact of clinical pathway teaching combined with objective structural clinical examination (OSCE) on nursing performance and clinical competence of new ICU nurses: a quasi-experimental study - Yingying Gao; Xiaorong Ding; Jiaqing Xu; Wenting Zhang; Ying Huang; Minhua Mo; Yanyan Li (BMC Nursing)
Abstract Background Due to the theory-practice gap, new ICU nurses often struggle to manage critically ill patients and high-risk conditions. While structured training programs exist, they lack standardized content and implementation path. This study aims to explore the impact of clinical pathway teaching combined with OSCE on new ICU nurses’ nursing performance and clinical competence. Methods Used sampling, a quasi-experimental with non-randomized two-group study design. We selected new nurses (n = 52) who joined their ICU from August 2020 to January 2022 and divided the subjects chronologically into two groups. The experimental group used clinical pathway teaching combined with the OSCE evaluation, while the control group took the routine method. We used the six-dimension scale of nursing performance scale (6-D) and the Nursing Clinical Competence Questionnaire (CNCQ) to collect the new ICU nurses’ data before and after a two-month training cycle. Statistical analysis was performed using t-tests and χ2-test, with a significance level set at P < 0.05. Results After training, the nurses of the experimental group had higher scores on the Nursing Clinical Competence Questionnaire (93.46 ± 11.20) compared to the control group (85.92 ± 12.19), and this difference was significant (P < 0.05). The nurses of the experimental group had lower scores on the 6-D scale before training (154.19 ± 38.32) compared to the control group (187.15 ± 32.20), the difference was significant(P < 0.05), but there was no significant difference after training (P>0.05). Conclusion Clinical pathway teaching combined with OSCE improve the clinical competence of new ICU nurses, and promote nursing performance. However, job experience and clinical environment might influence nursing performance.